Effect of temporal variation in precipitation on the demography of four herbaceous populations in a tropical dry forest area in Northeastern Brazil - Andrade da Silva, Kleber; Ramos de Andrade, Juliana; Falcão Fraga dos Santos, Josiene Maria; Gomes Reis Lopes, Clarissa; Nogueira Ferraz, Elba Maria; de Albuquerque, Ulysses Paulino; de Lima Araújo, Elcida (Revista de Biología Tropical, 2015)
In tropical dry forests, the dynamics of herbaceous populations is strongly influenced by seasonal and annual variation in total rainfall. Moreover, the present and past events of climatic anomalies (e.g. severe drought years and erratic rain before the growth season) may cause drastic reductions in population size, leading to the temporal disappearance of some species. Therefore, this three-year study aimed to assess the dynamics of Delilia biflora (Asteraceae), Commelina obliqua (Commelinaceae), Phaseolus peduncularis (Fabaceae) and Euphorbia heterophylla (Euphorbiaceae). The study was conducted in an area of tropical dry forest known as Caatinga, situated in the experimental station of the Pernambuco Agronomic Institute (IPA), in Caruaru, Pernambuco, Brazil. The Caatinga has a semiarid climate with strong seasonal and annual variation in total precipitation. During this study, there was a climatic anomaly event called the 2006 drought, and also erratic rains in the dry season. The birth, death and survival of plants were evaluated monthly using 105 plots (1 × 1 m). Differences in density between years and seasons were evaluated using the Kruskal-Wallis test. The explanatory power of present and past precipitation on density was evaluated using the General Linear Model. In this study, we present the first record of Euphorbia heterophylla in the studied area. The studied populations were larger during the rainy seasons and in wet years, and were drastically reduced in the driest year and dry seasons. Commelina obliqua was the least sensitive to variation in total rainfall. Regarding the variation in density, all four species were present during all three years. Birth rates were higher during the rainy season, and death rates were higher in the dry season. Sporadic rain in the dry season caused pronounced seedling recruitment followed by death, and had a strong impact on the dynamics of D. biflora, E. heterophylla and P. peduncularis. The precipitation of the current year explained between 3 % - 18 % of the inter-annual density variation, and the explanatory power of the previous year precipitation on the density of populations ranged from 32 % to 67 %. Therefore, climatic events of the past also have a significant consequence over the four populations. In conclusion, drastic reduction in total precipitation between years may be considered as a predictive parameter for herbaceous plants population size (in the present and future time) in a Northeastern Brazilian tropical dry forest area.